Case report: Bipolar disorder in 48,XXYY syndrome - Razali, Nur Atikah; Mohd Daud, Tuti Iryani; Woon, Luke Sy-Cherng; Mohamed Saini, Suriati; Muhammad, Noor Azimah; Sharip, Shalisah (Frontiers in Psychiatry, 2023)
48,XXYY syndrome is a rare condition. The presentations of impulsive and aggressive behavior have been reported in several case reports among patients with 48,XXYY syndrome. The management of the psychological impact and neuropsychiatric sequela of this condition is a significant issue faced by families, carers, and healthcare professionals. We report a patient, 21-year-old Malay male, with underlying 48,XXYY syndrome with attention deficit hyperactivity disorder (ADHD) and intellectual disability, diagnosed later in adulthood with a bipolar mood disorder and benefited after being started on lithium. We describe the key clinical features and diagnostic workouts that allowed the arrival of the correct psychiatric diagnosis. Challenges in psychopharmacotherapy, including the risks of metabolic syndrome and deep vein thrombosis associated with 48,XXYY syndrome, are also considered. We suggest that for patients with 48,XXYY syndrome, routine psychological screening for mood symptoms such as mania and depression should be done by healthcare professionals with early involvement of psychiatrist in the multidisciplinary team due to the challenges in the management of these patients.